سیاست اور قانون میں عدل و انصاف اور اس کے تقاضے: ایک تحقیقی وتجزیاتی مطالعہ: Justice and its demands in politics and law, an exploratory and analytical study - Altafur Rehman; Shahid ur Rahman; Hussain Ahmad (Al Manhal Research Journal, 2023)
There is no doubt that Islam is a universal and comprehensive system of life, it is a religion that is compatible with the conditions and requirements of all times, and is inclusive of the rules of various areas of life, and Islam related to each area of life. There are instructions. One of the major commands is justice and fairness. The position of "justice and justice" is like the backbone for running the Muhammadan system. Without justice, the reformation of the people is not possible. So, it is as if the stability of the government, politics, court and economic affairs is "justice" and this the downfall begins with tyranny. From the beginning of his collective life, man has started the process of creating and enforcing "laws and regulations". It is obvious that the fair use of laws is central to turning chaos and disorder into peace and stability. Justice is among these principles. It is from the fact that those who are established by Islam are not only in the system of government, but in the relationship of the individual with himself and the people. It is important for the subjugated to hold the ground and to be committed to justice and fairness from the beginning of his collective life, man has started the process of creating and enforcing "laws and regulations". It is obvious that the fair use of laws is central to turning chaos and disorder into peace and stability. Justice is among these principles. It is from the fact that those who are established by Islam are not only in the system of government, but in the relationship of the individual with himself and the people. It is important for the subjugated to hold the ground and to be committed to justice.